Fremantle on the Edge: A Community Collaboration - Farren, Anne; Spanbroek, Nancy (Springer, 2014)
This chapter addresses community engagement presented through a large local, inner urban project held in the City of Fremantle in 2009. It was an ambitious project with many challenges. This is a timely reflection on the benefits and pitfalls of a project of this scale, which included a large community-based exhibition presented in sites throughout the city and a closing event that became an interactive performance engaging both exhibitor and viewer. The project was carried out within a very tight time frame of 5 months from conception through to completion, and required the coordination of a complex set of inter-related tasks associated with the securing of funding, liaison with key stakeholders and general management of the processes associated with working with community and the presentation of a range of events that, on reflection, represented a mini festival.